À l’heure de l’information : le centre de documentation de Sodarcan Inc. - Dumont, Monique (Assurances)

(untitled) (HEC Montréal, 1986)
In days gone by, we had to refer to external sources, often great in number, to gather the details needed for a particular insurance or reinsurance file. Sodarcan took the initiative to create a Documentation Centre which can be used by both its departments and its clients. In this article, Miss Monique Dumont, Director, explains how the Centre operates, how it is staffed and what services it offers.